2016
DOI: 10.21037/acs.2016.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Transition from multiple port to single port video-assisted thoracoscopic anatomic pulmonary resection: early experience and comparison of perioperative outcomes

Abstract: Background: Single port thoracoscopy is an approach aimed at minimizing trauma to the chest wall during lung resection. The objectives of this study were to describe early experience in the transition from multiple port video-assisted thoracic surgery (VATS) to single port surgery (S-VATS) and to compare perioperative outcomes between approaches.Methods: Consecutive anatomic lung resections using S-VATS were reviewed and compared to a historical, prospective cohort of multiple port VATS cases. Outcomes analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 23 publications
2
17
0
1
Order By: Relevance
“…Uniportal lobectomy did not increase postoperative morbidity, indicating that it was safe and feasible, yielded enhanced postoperative recovery, and could achieve satisfactory early clinical outcomes. This data is consistent with a previous report, which indicated that conversion from multiple port VATS to single port surgery is safe, efficient, and of high surgical quality . However, more long‐term data are required.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Uniportal lobectomy did not increase postoperative morbidity, indicating that it was safe and feasible, yielded enhanced postoperative recovery, and could achieve satisfactory early clinical outcomes. This data is consistent with a previous report, which indicated that conversion from multiple port VATS to single port surgery is safe, efficient, and of high surgical quality . However, more long‐term data are required.…”
Section: Discussionsupporting
confidence: 92%
“…This data is consistent with a previous report, which indicated that conversion from multiple port VATS to single port surgery is safe, efficient, and of high surgical quality. 9 However, more long-term data are required. Alternative approaches to performing thoracoscopic lung resection should be carefully evaluated and compared to establish minimally invasive techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al 17 found no significant differences in the number or locations of total lymph nodes between the uniportal and three-portal groups. Additionally, French et al 18 found no significant differences in the number of total lymph nodes between the uniportal and three-portal groups. In our opinion, due to improvements in the surgical technique and apparatus, most thoracic surgeons would be able to reach similar lymph node dissection ranges as with three-portal thoracoscopy and open operation after completing the learning curve for uniportal thoracoscopic surgery.…”
Section: Discussionmentioning
confidence: 91%
“…found no significant differences in the number or locations of total lymph nodes between the uniportal and three‐portal groups. Additionally, French et al . found no significant differences in the number of total lymph nodes between the uniportal and three‐portal groups.…”
Section: Discussionmentioning
confidence: 95%
“…Uniportal VATS lobectomy is not related with a better postoperative outcome when compared with two or three-port approach (18). However, this technique can be considered safe and feasible (19).…”
Section: Introductionmentioning
confidence: 97%